MANAJEMEN DATA AKADEMIK PERGURUAN TINGGI KEAGAMAAN ISLAM SWASTA (STUDI LITERATURE REVIEW) - Abdullah, Musrizal; Zulfikar, Teuku; Shadiqin, Sehat Ihsan (An-Nadzir : Jurnal Manajemen Pendidikan Islam, 2024)
Data management also has a key role in ensuring institutional transparency and accountability. With accurate and reliable academic reporting, Islamic Higher Education can build trust in the community, prospective students, and other stakeholders. The method used in this research is the SLR (Systematic Literature Review) approach. By applying this strategy, researchers identify, analyze, evaluate, and interpret all research relevant to the chosen topic. The results of this research are that academic data management must comply with applicable legal regulations, especially in terms of data protection, privacy rights, and higher education regulations. Compliance with the law helps avoid potential legal issues that could arise from privacy violations or misuse of data. Ethics plays an important role in managing academic data. Openness, honesty, and respect for individual privacy must be the main principles in all data-related activities. Clear and upheld ethical policies can create an environment that is by religious and moral values. Academic data management is not only about legal and ethical compliance but also about improving operational efficiency. This system helps simplify administrative processes, facilitate strategic decision-making, and improve the quality of service to students, lecturers, and staff. Islamic Religious Universities need to integrate technology wisely in academic data management.